Measurements and time reversal in objective quantum theory - Belinfante, F. J. (Frederik Jozef) (International series in natural philosophy, 1975)
Measurements and Time Reversal in Objective Quantum Theory is a three-chapter book that begins with a discussion on the fundamentals of conventional quantum theory. The second chapter focuses on the time arrow of quantum theory. It specifically presents a schematized account of the results of an interesting paper on time reversal in quantum theory published by Aharonov, Bergmann, and Lebowitz. The last chapter presents the authors' conclusions and additional comments in this field. This book will be valuable to students of wave mechanics and will serve as a supplement to textbooks, which fail.